Comparative Analysis of the Two Ray Field Strength on Radio Mobile Itm Model and Recommendation Itu-R P.1546 - Kaschel-Carcamo, H; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2021)
This document represents the continuity of a research series on the behavior of radio propagation by the Irregular Terrain Model (ITM) from National Telecommunications Institute (NTI - USA), under certain operation conditions known as the 2-Ray mode on Line of Sight links (LOS). The research has been conducted on 24 links under several LOS conditions and terrain data. Then compared with ITU s (International Telecommunications Union) P.1546 and conclusions have been extracted and procedures recommended. Future work will include further research with new terrain data available from NASA. © 2021 IEEE.